Juridical Review Of The Case Of Alleged Plagiarism Of The Song "Apa Sih" By The Band Radja Against The Song "APT" By Rosé BLACKPINK Feat. Bruno Mars According To Law Number 28 Of 2014 Concerning Copyright. - Lasmana, Indra; Hayati, Mulida; Sudiarti, Elin (Journal of Law, Politic and Humanities, 2025)
This research is a juridical perspective on the case of alleged plagiarism of the song "Apa Sih" owned by Radja Band against the song "APT" owned by Rosé BLACKPINK feat. Bruno Mars within the framework of Law Number 28 of 2014 concerning Copyright. The development of digital technology has revolutionized the music industry, making it easier to reproduce and distribute works, and increasing the risk of copyright infringement. Plagiarism in musical works-including melodies, arrangements, lyrics, and audiovisual elements-is a copyright infringement that is legally categorized as a tort. This research uses a normative juridical method by analyzing statutory provisions, particularly Law No. 28 of 2014, to assess the scope of protection for musical and audiovisual works, as well as to examine the legal implications of alleged unauthorized duplication. The results show that there are significant similarities in the musical and visual components of the two songs that can be interpreted as a violation of the creator's economic and moral rights. Although the legal framework has provided strong protection, the implementation of copyright in the field still faces various challenges, such as subjectivity in assessing musical similarity, low public legal awareness, and the need for clear standards of proof. This research recommends strengthening the implementation of copyright law, public education related to intellectual property rights, and stricter supervision of digital platforms to maintain the originality of copyrighted works.